2022
DOI: 10.3390/polym14071378
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Extraction Conditions on the Yield and Physico-Chemical Parameters of Pectin from Grape Pomace

Abstract: Grape pomace is one of the most abundant by-products generated from the wine industry. This by-product is a complex substrate consisted of polysaccharides, proanthocyanidins, acid pectic substances, structural proteins, lignin, and polyphenols. In an effort to valorize this material, the present study focused on the influence of extraction conditions on the yield and physico-chemical parameters of pectin. The following conditions, such as grape pomace variety (Fetească Neagră and Rară Neagră), acid type (citri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…As in the WM extract, GPs were attributed to celluloses and hemicelluloses of the cell walls of the grape pomace [ 39 , 40 ]. In the literature, few studies found extracted pectin or cell-wall material from grapes, and they mainly focused on the characterization of grape cell-wall composition and structure, and, in most cases, they used toxic and stronger extractants such as ammonium oxalate, nitric acid, or sulfuric acid [ 43 , 44 , 45 ]. However, our research aimed to obtain polysaccharide extracts that could be used in the food industry.…”
Section: Resultsmentioning
confidence: 99%
“…As in the WM extract, GPs were attributed to celluloses and hemicelluloses of the cell walls of the grape pomace [ 39 , 40 ]. In the literature, few studies found extracted pectin or cell-wall material from grapes, and they mainly focused on the characterization of grape cell-wall composition and structure, and, in most cases, they used toxic and stronger extractants such as ammonium oxalate, nitric acid, or sulfuric acid [ 43 , 44 , 45 ]. However, our research aimed to obtain polysaccharide extracts that could be used in the food industry.…”
Section: Resultsmentioning
confidence: 99%
“…The absorption bands at 3269 cm −1 , 3267 cm −1 and 3265 cm −1 indicated a broad stretching of O–H [ 38 ]. The FT-IR spectra in the wavenumbers of 1410 and 800 cm −1 are identified to as the ‘fingerprint region’ of carbohydrates, which enables the identification of major chemical groups in different polysaccharides [ 10 , 13 , 39 ]. Therefore, the absorption peaks at 1402 cm −1 , 1400 cm −1 and 1399 cm −1 were ascribed to the –CH bending of –CH 2 groups, –COO symmetric stretching and asymmetric and symmetric stretching vibrations of the carboxylate anion in the side of polysaccharide, respectively [ 40 , 41 ].…”
Section: Resultsmentioning
confidence: 99%
“…Generally, commercial pectin is extracted from different citrus peels, such as lemon, orange, lime, grapefruit (85.5%), apple pomace (14%) and a small proportion is attributed to sugar beet pulp (0.5%) [ 3 ]. Indeed, there are a lot of unconventional sources of pectin, including mango peels [ 6 ], banana peels [ 7 ], watermelon rinds [ 8 ], black carrot pomace [ 9 ] and grape pomace [ 10 ], mainly produced by agro-industrial processing. However, it is proper to mention that yield, physicochemical parameters, structural and functional features of pectin depend on the extraction technique applied and other characteristics (solid to liquid ratio, temperature, time, pH, solvent type) [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The methoxyl content (5.58 ± 0.88%) and EW values (149.26 g/mol) can be correlated with extraction parameters, such as pH and temperature, whereas some other parameters (such as citric acid and extraction time) affect the monosaccharides’ structures of pectin, leading to a low value for EW [ 31 ]. Spinei and Oroian [ 29 ] reported methoxyl content ranging from 3.98 to 6.18% for the pectin extracted from grape pomace.…”
Section: Resultsmentioning
confidence: 99%
“…The citric acid method proposed by Spinei and Oroian [ 29 ] was used for the extraction of pectin from freeze-dried apple pomace. Briefly, the freeze-dried apple pomace was mixed with ultrapure water (1:10 w / v ), the pH of this mixture being adjusted to 2.0, and then kept, at 90 °C, for 3 h in a water bath (Julabo, Seelbach, Germany).…”
Section: Methodsmentioning
confidence: 99%